Carbón balance of PGR-IV-treated cotton plants - Cadena Torres, Jorge (Texas A & M University, 1995)
Cotton (Gossypium hirsutum L.) is a plant of tropical origin that is planted throughout the world for fiber production. Once planted it may be subjected to several environmental constraints like water stress, low and high temperatures, and nutrient shortage, conditions under which growth is affected and final yield reduced. Over the years, use of plant growth regulators in cotton production has been practiced. However, much of the work has been directed toward controlling growth rather than trying to enhance it. In the last 10 years industry has placed considerable emphasis on identifying chemical products that enhance cotton growth, especially when conditions are unfavorable. PGR-IV, a relatively new plant growth regulator, has been evaluated in cotton under a wide range of environmental conditions. This growth regulator is produced in a fermentation broth of soil bacteria, yeast, and fungi (Urwiler and Stutte, 1988) and contains synthetic indolebutyric acid (IBA) and gibberellic acid (GA) in a nutrient solution blend. Application of PGR-IV to cotton plants has resulted in increased root length, root dry weight, and number of lateral roots per plant (Oosterhuis and Zhao, 1993a, 1993b; Oosterhuis and Zhao, 1994), which lead researchers to the hypothesis that this plant growth regulator may enhance the capacity of the plant to sustain growth under unfavorable conditions, especially water stress (Zhao and Oosterhuis, 1994; Atkins, 1992; Livingston et al., 1992).